2012
DOI: 10.1016/j.ejcnurse.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A brief neuropsychological battery for use in the chronic heart failure population

Abstract: Background Cognitive impairment is a recognized consequence of heart failure; however, there are no neuropsychological batteries with documented psychometric data in the chronic heart failure population. Aims To document the psychometric properties of a brief neuropsychological battery in a chronic heart failure sample. Methods The Repeatable Battery for the Assessment of Neuropsychological Status, Trail Making Test Part A and Part B, and letter fluency was administered to a sample of individuals with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…Thus, our findings may not generalize to other populations, including younger, non-white individuals, inpatients, or those with Class I or IV HF, preserved EF, and/or lower education levels. Next, we did not use age- and education-matched data from individuals with chronic heart failure in our norming procedure; however, this limitation is mitigated by previous work documenting that age- and education-matched norms from non-HF populations is an acceptable alternative to having chronic HF controls [36]. Lastly, although we used a comprehensive neuropsychological battery assessing several cognitive domains, our assessment of visuospatial ability was comprised of a single test, thereby potentially reducing its validity and reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings may not generalize to other populations, including younger, non-white individuals, inpatients, or those with Class I or IV HF, preserved EF, and/or lower education levels. Next, we did not use age- and education-matched data from individuals with chronic heart failure in our norming procedure; however, this limitation is mitigated by previous work documenting that age- and education-matched norms from non-HF populations is an acceptable alternative to having chronic HF controls [36]. Lastly, although we used a comprehensive neuropsychological battery assessing several cognitive domains, our assessment of visuospatial ability was comprised of a single test, thereby potentially reducing its validity and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although these norms were not specific to HF populations, similar norming procedures have been used for other neuropsychological studies of patients with HF, and Bauer et al. [36] have indicated that using age- and education-matched norms from non-HF populations is an acceptable alternative to chronic HF controls. The scaled scores were converted to T-scores to facilitate interpretation ( M = 50, SD = 10).…”
Section: Methodsmentioning
confidence: 99%
“…In a population sample of community-dwelling adults (n = 650; age range: 75-85 years), individuals with HF at baseline were more likely to experience a significant decline in cognitive function over the subsequent 5 years (relative risk: 1.83; 95% CI: 1.02-3.27) than individuals without HF at baseline [114]. Difficulties with memory, attention, psychomotor speed, verbal learning and executive functions are the most common types of cognitive deficits reported in HF patients [115][116][117][118]. However, it is not clear whether there is a typical profile of cognitive deficits in HF patients or how this profile evolves over time [116].…”
Section: Epidemiology Of Chronic Forms Of Cognitive Impairment In Hfmentioning
confidence: 97%
“…Ambulatory outpatients onlyHF: 63 (14)Healthy controls: 63 (14)Case controlDiagnosis of HF >6 monthsCo-morbid psychiatric or neurological illnessLVEF ≤40%NYHA II-IVMultidomain neuropsychiatric batterySystolic HF pts scored lower than control group in domain of verbal memoryPressler 2010 [21]249 HF ptsAmbulatory outpatients onlyHF: 63 (15)Cross-sectionalHF: LVEF ≤40% and clinical HFCo-morbid psychiatric, neurological or physical illness. Previous diagnosis of CINYHAMultidomain neuropsychiatric batteryHF group performed worse than healthy and general medical groups in domains of memory, executive function and psychomotor speed63 healthy controlsHealthy controls: 53 (17)Healthy controls: absence of any medical condition or controlled CV risk factorsLVEF102 general medical ptsMedical group: 63 (12)Medical group: major chronic disorder other than HFBauer 2012 [22]51 HF-REF, 29 HF-PEFAge >21 years and ambulatory outpatients only72 (12)Cross-sectionalHF-REF: history of HF-REF >6 months, stable on medication >4 weeks, LVEF ≤40%Co-morbid psychiatric, neurological or physical illness. Previous diagnosis of CILVEFMultidomain neuropsychiatric batteryHF-REF and HF-PEF pts performed worse than age- and educated-adjusted healthy control groups in executive function, attention, language, memory and psychomotor speedHF-PEF: history of HF-PEF >6 months, stable on medication >4 weeks, LVEF >41%NYHAFesta 2011 [23]169 HF-REF, 38 HF-PEFAge >17 years and ambulatory outpatients only69RetrospectiveOn medical treatment for HFCo-morbid neurological illnessLVEFMultidomain neuropsychiatric batteryLow EF was associated with poor memory in pts over 63 years oldHaemodynamically stablePts <63 years old had preserved memory function regardless of EF.Not receiving mechanical circulatory supportSteinberg 2011 [24]55 HF ptsAmbulatory outpatients only55 (8)Cross-sectionalStable clinical statusCo-morbid neurological or physical illness.…”
Section: Heart Failure and Cognitive Impairment – Strength Of Associamentioning
confidence: 99%